Jūreiviai - tarybinės literatūros propaguotojai ir platintojai užsienyje - Starkūnaitė-Jurkuvėnienė, Vanda; Česnulevičiūtė, Dana (Knygotyra, 1985)
The article deals with the problem of the activities of various institutions of Klaipėda, such as the Sailors’ International Club of the Merchant Port of Klaipėda, the Union of the Lithuanian Fish Industry, and the Lithuanian Shipping Company, in spreading and propagating Soviet Lithuanian publications abroad. Many people abroad want truthful information about this country, and our sailors and the guides of the International Club who have immediate contacts with foreigners help them in getting various Soviet publications the motto of which is: “Books for Peace and Progress”. In the article the peculiarities of the international activities of the above mentioned institutions, the collective members of the Lithuanian Society for Cultural Relations with Foreign Countries, are revealed, also many facts based on the published data show the foreigners’ great interest in the life of the peoples of the Soviet Union, in Soviet newspapers and magazines, particularly in social and political literature, books for children and belles-lettres. The article also analyses the geographical factors of the sailors’ activities. A conclusion is drawn that there is a great shortage of publications about Soviet Lithuania, that there is an urgent need for more Lithuanian illustrated books in Portuguese, Spanish, Danish, Swedish, and French. The Soviet sailors represent the Lithuanians and many other Soviet nations. Thus, their activities in spreading and exhibiting Soviet publications on the boards which propagate that “Every book can be a souvenir” are of great importance: they give information to people abroad about the peaceful foreign policy of the Soviet State, about the Soviet way of life, etc. These activities help to win more friends for our country.